2014
DOI: 10.1186/s12929-014-0101-3
|View full text |Cite
|
Sign up to set email alerts
|

N-3 polyunsaturated fatty acids decrease levels of doxorubicin-induced reactive oxygen species in cardiomyocytes -- involvement of uncoupling protein UCP2

Abstract: BackgroundUse of the chemotherapeutic drug doxorubicin (DOX) is associated with serious cardiotoxicity, as it increases levels of reactive oxygen species (ROS). N-3 polyunsaturated fatty acid dietary supplements can be of benefit to patients undergoing cancer therapy. The aims of this study were to determine whether DOX-induced cardiotoxicity is related to mitochondrial uncoupling proteins and whether eicosapentaenoic acid (EPA, C20:5 n-3) or docosahexaenoic acid (DHA, C22:6 n-3) affects DOX-induced cardiomyoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 43 publications
(52 reference statements)
2
31
0
Order By: Relevance
“…Previous studies indicate that surplus palmitate induces ROS production, energy shortage, inflammation, ER stress and autophagy dysregulation and eventually causes mitochondrial dysfunction and triggers apoptosis . However, Hsu et al indicated the incorporation of fatty acid into subcellular fractions needs 24‐48 hours . Hence, in the future, DRP1 knockdown studies in cells must investigate the fatty acid composition of mitochondrial membranes as well as other mechanisms (eg ER stress, autophagy) with short‐term or long‐term palmitate stress to clarify the potential mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that surplus palmitate induces ROS production, energy shortage, inflammation, ER stress and autophagy dysregulation and eventually causes mitochondrial dysfunction and triggers apoptosis . However, Hsu et al indicated the incorporation of fatty acid into subcellular fractions needs 24‐48 hours . Hence, in the future, DRP1 knockdown studies in cells must investigate the fatty acid composition of mitochondrial membranes as well as other mechanisms (eg ER stress, autophagy) with short‐term or long‐term palmitate stress to clarify the potential mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…48,54 However, Hsu et al indicated the incorporation of fatty acid into subcellular fractions needs 24-48 hours. 55 Hence, in the future, DRP1 knockdown studies in cells must investigate the fatty acid composition of mitochondrial membranes as well as other mechanisms (eg ER stress, autophagy) with short-term or long-term palmitate stress to clarify the potential mechanism.…”
Section: Limitationsmentioning
confidence: 99%
“…To determine the fatty acid composition, lipids were extracted from the adipose tissue according to Hsu et al 13 Each sample (50 mg) plus 50 lg of 1,2-dinonadecanoylsn-glycero-3 phosphocholine (C19:0 PC; Avanti Polar Lipids Inc.; Alabaster, Alabama), as an internal standard was homogenized in a 2/1/0.75 (v/v/v) mixture of methanol/chloroform/water, centrifuged and the upper phase discarded. The lower phase was dried under nitrogen.…”
Section: Determination Of Fatty Acid Compositionmentioning
confidence: 99%
“…Components were identified by comparison of the retention time with those of authentic standards (Supelco 37 Comp. Fame Mix TM , Supelco Inc. Belletonte PA) 13.…”
mentioning
confidence: 99%
“…One of the ways Doxorubicin is thought to mediate cardiac cell apoptosis is through the intrinsic pathway, initiated in the mitochondria. Hsu et al (2014) have demonstrated that Dox causes a loss of Δψm in H9C2 cardiomyocytes and restoration of Δψm by treatment with polyunsaturated fatty acids prevents cell death induced by Dox. Treatment with Dox caused loss of Δψm in the present study.…”
Section: Discussionmentioning
confidence: 99%